Preparation and Photocatalytic Activity of 3D Flower like MoS2/Fe2O3 Nano Heterostructures - JIANG Jiuxing; YAN Junjie; SUN Yu; WANG Shu (Journal of Harbin University of Science and Technology)
MoS2/Fe2O3 nanocomposites were prepared by twostep hydrothermal method The structure, morphology, surface chemical composition and optical properties of MoS2/Fe2O3 composites were systematically characterized It was found that when the atomic ratio of Mo/Fe was increased to more than 3∶1, the morphology of the composites presented a unique threedimension flowerlike structure, and the existence of the nanoheterostructure could be confirmed by HRTEM XRD analysis showed that the phase structure of the composites was composed of hexagonal hematite Fe2O3 and molybdenite MoS2 without any impurity phase In addition, PL results illustrated that the separation of photogenerated electronhole pair was effectively accelerated by the effect of heterostructure Therefore, MoS2/Fe2O3 nanocomposites exhibited excellent photocatalytic performances, among with 30 at% MoS2/Fe2O3 possessed the best photocatalytic activity on photodegrading 20 mg/L methylene blue solution within 20 min, which was almost 10 times than bare Fe2O3 nanoparticals